PETROLOGICAL AND GEOCHEMICAL FEATURES OF THE MELIATA MAFIC ROCKS FROM THE SUTURED TRIASSIC OCEANIC BASIN, WESTERN CARPATHIANS - Faryad, Shah Wali; Spišiak, Ján; Horváth, Péter; Hovorka, Dušan; Dianiška, Ivan; Józsa, Sándor (Ofioliti, 2005)
Metabasites related to the Triassic Meliata oceanic basin occur along three tectonic zones in the Western Carpathians: (1) the Folkmár Zone, (2) the Roz?n?ava Zone (Meliata Unit, s.s.) and the (3) Bódva valley - Darnó Hill Zone. The first two zones form the northern and southern boundary of the Paleozoic of the Gemericum (south-eastern Slovakia), respectively, and the latter is located south of the Meliata Unit, NE Hungary. All three zones contain metabasites. The serpentinites, radiolarian shales and cherts are considered to be complementary members of an ancient oceanic crust. Geochemical characteristics of metabasites from the Folkmár Zone indicate a MORB affinity. Metabasites from the Roz?n?ava Zone have affinity between MORB and within plate basalts, but metagabbros comparable with alkaline basalts are also present. The Darnó Hill metabasites have MORB compositions and those from the Bódva valley are similar to the metabasites from the Roz?n?ava Zone. The geochemical and petrographic features of these metabasites suggest a continental rift volcanism, followed by spreading of the Triassic Meliata oceanic basin. During the Middle Jurassic, part of the oceanic crust and adjacent passive continental margin underwent a subduction-related blueschist facies metamorphism afterwards they were exhumed within a mélange complex of the Meliata Unit in the southern part of Gemericum.